THE EFFECTIVENESS OF INTERACTIVE ANIMATION MULTIMEDIA IN INCREASING THE LEARNING MOTIVATION OF GRADE V STUDENTS - Tatik Sugiwati Tatik; Ardi Samudra Rochmattulloh Ardi (SOSIOEDUKASI, 2024)
This study aims to find out how much influence interactive animation multimedia has in increasing the learning motivation of class V students in school cluster 05 Banyuwangi District, which consists of SDN Tamanbaru, SDN Kebalenan, SDN Sobo, SDN Sumberrejo, SDN Kertosari 1, SDN Kertosari 2 dan SDN Model. Sampling was conducted using random sampling with a shaking system. So, the experimental class and the control class were chosen. The results of the study show that: 1) The validity of the learning motivation questionnaire is very valid r calculate > r table; 2) The reliability of the X variable is 0.926, and the Y is 0.845 Excellent and Good Reliable Categories; 3) Homogeneous; 4) Normally distributed; 5) there is a linear relationship between the independent variable and the bound variable; 6) There is a positive influence between the use of interactive animation multimedia on learning motivation. So, interactive animation multimedia has an effective impact on learning motivation by 71.3%.